Health-related quality of life of patients after ischaemic stroke treated in a provincial hospital in Poland - Szymon Jarosławski; Bożena Jarosławska; Barbara Błaszczyk; Pascal Auqier; Mondher Toumi (Taylor & Francis Group, 2020)
Background Ischaemic stroke (IS) is a major cause of death and disability and affects the quality of life of patients. Previous studies focused on urban populations. Objective To evaluate the health-related quality of life (QoL) of patients with history of IS and living in a rural area in Poland. Patients Rural population of 172 patients discharged from a district hospital in Zakopane, Poland with a diagnosis of IS in the period from 01.01.2005 to 31.10.2006. Intervention QoL was evaluated using the European Quality of Life Scale-5 Dimensions EQ-5D-3 L (EQ-5D) and the Short Form Health Survey - 12 version 2 (SF-12). Results In the EQ-5D survey, 57.3% of patients had only some problems with mobility, 40.3% with usual activities, 63.2% with pain/discomfort, 59% with anxiety/depression, and 32.2% with self-care. In the SF-12 survey, both summary components (physical and psychological) were reduced compared to the population norm. Conclusion The quality of life in IS survivors is clearly reduced in the majority of domains assessed by the EQ-5D and SF-12 questionnaires. The most important factors affecting QoL were the functional state, depression and anxiety. A significant difference as compared to to urban and mixed populations was observed for a reduced SF-12 mental health component and for the EQ-5D visual analogue scale. We found no effect of gender, age or cognitive disorders on the outcomes of SF-12.